Fatigue Assessment and Deterioration Effects on Masonry Elements: A Review of Numerical Models and Their Application to a Case Study - Casamassima, Vito Michele; D'Amato, Michele (Frontiers in Built Environment, 2019)
Safety assessment with respect to seismic and vertical loads of existing and very old masonry structures is currently a central topic for the scientific engineering community. In particular, there are many ancient bridges still in service that are subjected to higher and more frequent cyclic loads. For these structures, it is important to determine the actual fatigue strength, rather than the ultimate carrying capacity. In this way the remaining service life, with possible traffic load limitations, may be estimated. This paper reports an updated review of the state-of-the art on recently published fatigue models that account for deterioration effects under cyclic loads. In addition, results related to fatigue performance of a bridge are shown and comments are provided. The numerical comparisons among existing fatigue models reveal that the application of the available fatigue models is particularly problematic for ancient masonry elements, where appropriate stress-life curves are required.